1-(4-Amino-2-Hydroxyphenyl)Ethenone Suppresses Agrobacterium tumefaciens Virulence and Metabolism - Zhou, Jin-Wei; Jia, Ai-Qun; Tan, Xiao-Juan; Chen, Hong; Sun, Bing; Huang, Tian-Zi; He, Yu; Li, Pei-Li; Liu, En-Qi (Frontiers in Microbiology, 2020)
The impact of 1-(4-amino-2-hydroxyphenyl)ethanone (AHPE) from the metabolites of endophytic fungus Phomopsis liquidambari on quorum sensing (QS) of Agrobacterium tumefaciens was evaluated for the first time in this study. Exposure to AHPE at concentrations ranging from 12.5 to 50 µg/mL, the β-galactosidase activity, acyl-homoserine lactone level, swimming motility, chemotaxis, and flagella formation were significantly inhibited. qRT-PCR quantification combined with the docking analysis demonstrated that AHPE inhibited the QS system of A. tumefaciens by repressing the transcriptional levels of traI and traR rather than signal mimicry. 1H NMR-based metabolic analysis indicated that the metabolism of A. tumefaciens was notably disturbed with AHPE treatment. AHPE treatment also resulted in the enhanced oxidative stress in A. tumefaciens. The enhanced oxidative stress lead to the disorder of energy supply, protein synthesis, and nucleotide metabolism, and ultimately attenuated the pathogenicity of A. tumefaciens. Our study indicated that AHPE can serve as a potential pesticide to defend against A. tumefaciens.